MnO2 with controlled phase for use in supercapacitors. Issue 4 (10th January 2017) - Sari, Fitri Nur Indah; So, Pei‐Ru; Ting, Jyh‐Ming
Abstract: Nanostructured MnO2 has been synthesized using a simple and rapid microwave‐assisted hydrothermal (MHT) technique through the decomposition of KMnO4 in a hydrochloric acid solution. The effects of hydrothermal temperature and ramp rate were examined and discussed. It was found that a lower temperature (140°C) favors the formation of cauliflower‐like δ‐MnO2 particles while a higher temperature (160°C, 180°C, or 200°C) favors the formation of α‐MnO2 nanorods. The dimensions of the obtained MnO2 nanorods were affected by the ramp rate. The cauliflower‐like δ‐MnO2 particles have higher specific surface areas than the α‐MnO2 nanorods. Supercapacitors having the obtained MnO2 as the electrodes were evaluated using cyclic voltammetry and electrochemical impedance spectroscopy in a 1 mol·L −1 Na2 SO4 solution within a potential window of −0.1‐0.9 V. The cauliflower‐like δ‐MnO2 electrodes give higher capacitance, up to 202 F/g, than the nanorods α‐MnO2 electrodes, at most 61 F/g.